Analisis faktor yang berhubungan dengan kejadian infeksi Covid-19 pada tenaga kesehatan - Tenry Derma Pratama; Neno Fitriyani Hasbie; Achmad Farich; Vera Yulyani (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: The situation of Covid-19 in the world is still increasing. The number of cases in the world has more than 32,000,000 people and around 1,000,000 people have died. Indonesian data as of September 29, 2020 shows more than 280,000,000 covid-19 cases. The vaccination program launched by the government is an important part of dealing with the pandemic. Vaccines encourage the formation of specific immunity in the body to avoid contracting or possibly becoming seriously ill.Purpose: To analysis of infection status of health workers during the Covid-19 outbreakMethod: A quantitative study with the population is health workers at Dr.H. Abdul Moeloek Hospital, Lampung. The sampling technique used was a random sampling technique and took a sample of 254 Health Workers. The research instrument used a questionnaire.Results: The health workers who had been vaccinated against Covid-19 dose I and dose II got 100%. However, only 235 received the Booster vaccine. The type of vaccines taken that Sinovac and Moderna. 172 do not have comorbidities and most of them, duty in the yellow area zone of 76. There is no relationship between vaccine status, vaccine type, and comorbidities with the incidence of Covid-19. There is a relationship between duty area zones and the case of Covid-19 (p-value = 0.00).Conclusion: Most of the variables studied do have not a relationship with the occurrence of Covid-19 and the duty area zone variable has a relation with the occurrence of Covid-19.Keywords: Covid-19; Pandemic; Hospital; Health workersPendahuluan: Situasi Covid-19 di dunia masih terus meningkat. Jumlah kasus di dunia sudah lebih dari 32.000.000 orang dan sekitar 1.000.000 orang meninggal. Data Indonesia sampai pada 29 September 2020 menunjukkan lebih dari 280.000.000 orang kasus Covid-19. Program vaksinasi yang dicanangkan pemerintah menjadi bagian penting untuk mengatasi pandemi. Vaksin mendorong pembentukan kekebalan spesifik tubuh agar terhindar dari tertular ataupun kemungkinan sakit berat.Tujuan: Untuk menganalisis status infeksi tenaga kesehatan selama wabah Covid-19Metode: Penelitian kuantitatif dan populasinya tenaga kesehatan di RSUD Dr.H. Abdul Moeloek Provinsi Lampung tahun 2021. Teknik pengambilan sampel menggunakan teknik randome sampling dan didapatkan sampel berjumlah 254 responden. Instrumen penelitian menggunakan kuisioner.Hasil: Tenaga kesehatan yang telah melakukan vaksinasi Covid-19 dosis I dan dosis II didapatkan 100%. Namun hanya 235 orang yang mendapat vaksin dosis Booster. Jenis vaksin yang didapat yaitu Sinovac dan Moderna. Responden tidak memiliki komorbid sebanyak 172 orang, bekerja pada zona kerja kuning 76 orang. Tidak terdapat hubungan antara Status vaksin, jenis vaksin, dan komorbid dengan kejadian Covid-19. Terdapat hubungan antara zona kerja dengan kejadian Covid-19 (p-value=0,00).Simpulan : Beberapa variabel tidak didapatkan hubungan antara status vaksin, jenis vaksin,dan komorbid dengan kejadian Covid-19, namun terdapat hubungan antara Zona Kerja dengan kejadian Covid-19.